2013
DOI: 10.1186/1471-2466-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of treatment with high-frequency chest wall oscillation in patients with bronchiectasis

Abstract: BackgroundHigh-frequency airway clearance (HFCWC) assist devices generate either positive or negative trans-respiratory pressure excursions to produce high-frequency, small-volume oscillations in the airways.HFCWC can lead to changes in volume of 15–57 ml and in flow up to 1.6 L/s, which generate minimal coughing to mobilize secretions. The typical treatment lasts 20–30 minutes, and consists of short periods of compression at different frequencies, separated by coughing.The aim of this study was to find the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 43 publications
4
65
0
15
Order By: Relevance
“…Numerous studies come in agreement with our results and concluded that the reduction in CAT-score detects early health status improvement and chest wall vibration reduces dyspnea in COPD patients. 4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Numerous studies come in agreement with our results and concluded that the reduction in CAT-score detects early health status improvement and chest wall vibration reduces dyspnea in COPD patients. 4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization.…”
Section: Discussionsupporting
confidence: 78%
“…3 The improved spirometric-indices reported among our patients in HFCWO or Flutter with no improvement in control group (Table 3), was similar to the results reported by Nicolini et al, who concluded that, there was significant improvement in pulmonary function tests (FEV1 or FVC) in CPT and HFCWO treated patients in comparison to control group. 4 Conversely, Chakravorty et al, found no significant change in baseline spirometricindices (FEV1 or FVC) with HFCWO versus postintervention ones. 7 Mahajan et al, and Holland et al, reported that the vest HFCWO device was well tolerated with improvement in ventilatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment should be included among the principal options in chest physiotherapy [13]. There was a significant improvement of FVC and FEV1 also arterial oxygen pressure (PaO2), carbon dioxide pressure (PaCO2) improved after 4 weeks in patients with chronic obstructive pulmonary diseases (COPD) after upper abdominal surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…The OPEP provide an improvement both in pulmonary function tests (FVC, FEV1) and quality of life. This treatment should be included among the principal options in chest physiotherapy [13].…”
Section: Discussionmentioning
confidence: 99%